ALAT PEMANTAU LOKASI DAN KESEHATAN LANSIA BERBASIS INTERNET OF THINGS - Delima Ayu Anugrah; Herlambang Saputra; Ica Admirani (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2026)
The elderly population in Indonesia increases yearly, along with health risks and potential disorientation due to cognitive decline. Therefore, a wearable, remotely accessible device is needed to monitor both location and vital signs. This study aims to design an IoT-based wearable device that monitors body temperature, heart rate, and oxygen saturation of elderly individuals, along with real-time location tracking via the Telegram application. The device integrates MLX90614, MAX30100, and GPS NEO-6M sensors controlled by a Wemos D1 Mini microcontroller connected through a 4G modem. Data is sent automatically every three hours and can also be requested manually using the "#kondisi" and "#lokasi" commands. The system was tested on three elderly age groups. Results showed that the device accurately detected body temperature with up to 100% success, heart rate within 80–100% normal range, and reliable oxygen saturation levels. Telegram-based notifications functioned well for both periodic updates and emergency alerts. Therefore, this tool effectively supports families in accurately and efficiently monitoring the health and whereabouts of elderly individuals.